2011
DOI: 10.1002/stem.611
|View full text |Cite
|
Sign up to set email alerts
|

Concise Review: Induced Pluripotent Stem Cells and Lineage Reprogramming: Prospects for Bone Regeneration

Abstract: Bone tissue for transplantation therapies is in high demand in clinics. Osteodegenerative diseases, in particular, osteoporosis and osteoarthritis, represent serious public health issues affecting a respectable proportion of the elderly population. Furthermore, congenital indispositions from the spectrum of craniofacial malformations such as cleft palates and systemic disorders including osteogenesis imperfecta are further increasing the need for bone tissue. Additionally, the reconstruction of fractured bone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 127 publications
(165 reference statements)
0
40
0
Order By: Relevance
“…The relationship between DPPSCs and iPS cells should also be investigated. The induction of iPS cells seems to be easier from stem cells than from differentiated cells (Illich et al, 2011). It could be that a reprogramming process occurs in DPPSCs, but not in differentiated dermal fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between DPPSCs and iPS cells should also be investigated. The induction of iPS cells seems to be easier from stem cells than from differentiated cells (Illich et al, 2011). It could be that a reprogramming process occurs in DPPSCs, but not in differentiated dermal fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…These approaches are still in their infancy as new vectors are required to prevent tumorigenesis that may be due to insertional mutations. 64 New vectors have been developed and nonviral approaches, such as gene activated matrices, are also promising. 114 …”
Section: Systemic Versus Local Delivery Of Cells For Bone Repairmentioning
confidence: 99%
“…64,87 These cells can all be induced into osteoblasts or chondrocytes in vitro. In the study by Zhang et al, human fetal MSCs (hfMSCs) were shown to augment healing of rat critical-sized defects via stimulating vascularization.…”
Section: Main Cell Sources For Bone Tissue Engineeringmentioning
confidence: 99%
“…plasminogen activator; bone repair; osteoblast; cell proliferation; vessel formation ALTHOUGH AN AUTOGENOUS BONE GRAFT is the gold standard procedure for the reconstruction of a bone defect, it has several disadvantages, including the limited size of the graft and injury to the donor site (23). Fractures are one of the most frequent injuries of the musculoskeletal system.…”
mentioning
confidence: 99%